ANALISIS PEMILIHAN SUMBER DANADALAM PENAMBAHAN AKTIVA TETAPANTARA LEASINGDENGAN KREDIT BANKPADA PENTA MEDICA - Artana, Ketut Wijaya; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2015)
ABSTRACT This study discusses  about Penta Medica which is considering alternative funding to increase investment vehicle such as a car unit operations to improve their company's performance. Penta Medica uses beyond the company's source of funds is through a bank loan or leasing. The purpose of this study was to determine the more favorable funding sources between bank loans and leasing. This study use traditional comparative descriptive analysis techniques, by comparing the PV of the cash out flow between bank credit and leasing. Variables used consists of bank interest rates, interest rate leasing, installment debtors, car purchase price, credit period and cash out flow. Based on the results of analysis show that the PV of the cash out flow of bank credit of Rp 254,250,777.63 while for the leasing of Rp 256,198,993.37. So the present value of the cash out flow is lower than leasing. It can be concluded that the use of bank credit financing is more advantageous than leasing. Keywords : credit, leasing, present value
Keywords: credit; leasing; present value